EFFECT OF VIRGIN COCONUT OIL ON MYCOBACTERIUM SMEGMATIS AND STAPHYLOCOCCUS AUREUS TREATED WITH EXTRACTS OF ZANTHOXYLUM ACANTHOPODIUM FRUIT - JULISTIONO, HEDDY; SUSENO, INTAN PERMATASARI; HANDAYANI, NURUL; HANDAYANI, RINI; DEWI LOTULUNG, PUSPA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: To understand the potency of herbal formulation of virgin coconut oil (VCO) and andaliman (Zanthoxylum acanthopodium) fruit activity against microbes, effects of ethylene acetate and hexane extracts of fruit of andaliman on viability and ions leakages of Mycobacterium smegmatis dan Staphylococcus aureus treated with VCO has been investigated. Methods: Antibacterial activity of extracts of andaliman fruit, or VCO, or andaliman and VCO against M. smegmatis and S. aureus was investigated using MTT assay method. Membrane disruption of bacterial cells treated with the plant extract and VCO was determined by measuring potassium and sodium ions leakages using Atomic Adsorbtion Spectrophotometer. Results: VCO of 512 μg/ml did not have antibacterial activity. In M. smegmatis treated with andaliman hexane extract, presence VCO decreased both ions leakage whereas in S. aureus treated with ethyl acetate extract only sodium ion was decreased. In both microorganisms, VCO could not protect cells of both M. smegmatis and S. aureus from death caused by andaliman extracts. Conclusions: VCO prevented ions leakages of the bacteria treated with extract of andaliman but did not protects cells from death.